Evaluation results of pasture condition of Battsengel soum, Arkhangai aimag - D, Orkhontamir; D, Tumenjargal (Mongolian Journal of Agricultural Sciences, 2018)
The winter of 2016 was cold, snowy, summer is hot and rainy, compared to 2011-2015 average in Battsengel soum. In 2017 the winter is warmer, summer is less hot and precipitation than in 2016. In territory of 6 bags of Battsengel soum observed 23 pasture types. There are 13-44 species per 100 m2 of pasture, including 2-8 species indicating pasture degradation. In the pasture area of Batsengel soum were recorded 87 species of plants belonging to 24 families and 61 types, including 15 species of indicating pasture degradation. In Batsengel soum, in 2016 the moisture was abundant and the vegetation coverage of the pasture was 56.55%, including the grasses was 23.18% and the bare land - 26.54%, and in hot and dry 2017 the vegetation cover was 38.01% which has level of grasses dropped to 11.86% and bare land increased to 41.44%. In 2016 the Battsengel soum had 324746 heads of livestock (623713.3 sheep heads) and in 2017 counted 372546 heads of livestock (713494.9 sheepheads) while the number of livestock increased in 13%. By increasing the number of livestock and climate condition the pasture carrying capacity was 1.7 times in 2016 and 3.5 times in 2017 over.